1996
DOI: 10.1289/ehp.961041070
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in pregnant women of high and low socioeconomic status in Mexico City.

Abstract: This study examined the determinants of blood lead (BPb) in 513 pregnant women in Mexico City: 311 from public hospital prenatal clinics, representing primarily women of low socioeconomic status (SES), and 202 from private hospitals, primarily women of high SES. Overall, BPb levels ranged from 1.38 to 29 micrograms/dl, with geometric means of 6.7 and 11.12 micrograms/dl for women from private and public hospitals, respectively. The crude geometric means difference obtained by t-test was 4.42 (p < 0.001). BPb w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
2
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 17 publications
1
30
2
2
Order By: Relevance
“…Seasonal variations in blood Pb levels have been observed in venous blood of adults and children (Farias et al, 1996;Laidlaw et al, 2005). In venous blood of 513 pregnant women of Mexico City (where climate and nutrition are quite different from Belgium): higher levels were measured during fall and winter, compared to spring and summer (Farias et al, 1996).…”
Section: Determinants Of Pollutant Levels In Cord Bloodmentioning
confidence: 99%
“…Seasonal variations in blood Pb levels have been observed in venous blood of adults and children (Farias et al, 1996;Laidlaw et al, 2005). In venous blood of 513 pregnant women of Mexico City (where climate and nutrition are quite different from Belgium): higher levels were measured during fall and winter, compared to spring and summer (Farias et al, 1996).…”
Section: Determinants Of Pollutant Levels In Cord Bloodmentioning
confidence: 99%
“…Thus, these agents may have the additional benefit of preventing increases in BPb levels commonly seen in these life stages. During pregnancy, calcium supplementation is associated with lower BPb levels (22)(23)(24), although calcium given alone has not been proven to reverse the loss of bone mineral density during pregnancy (24) or in postmenopausal subjects (25). In menopausal women, antiresorptive agents such as hormone replacement therapy (HRT) and bisphosphonates are capable of preventing loss of bone density (20,25,26).…”
mentioning
confidence: 99%
“…Among nonHispanic black 3-5-year-old children, the prevalence of blood lead levels of 10 pig/dl was 20.0% compared with 3.7% among non-Hispanic children (34). Nutritional status for minerals (especially low-calcium and low-iron status), quantity and type of macronutrients (e.g., high-fat intake), and less than adequate overall food intakes have been found to increase lead absorption [for a review, see Mahaffey (35) (32), and recently identified as a risk factor for elevated blood lead levels among pregnant women in Mexico City (38).…”
mentioning
confidence: 99%